Manusia Indonesia Menurut Pramoedya Ananta Toer : Studi atas Novel Bumi Manusia - Rahawarin, Ambrosius Andi (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2024)
The purpose of this study is to explore Pramoedya Ananta Toer’s concept of human being in his novel entitled Bumi Manusia. Bumi Manusia was written by Pramoedya to express his view on the situation of Indonesian society during colonization era. Using text study and critical reflection methods, this study finds that for Pramoedya, being human being means being a free and civilized person. Being human being means being a brave and knowledgeable person. This notion is still relevant for our era hence can be used for inspiration to build our society today.